Phylogenetic analysis of rabies surveillance samples from north and northeast Brazil - Cunha, Tânia Cristina Alves da Silveira da; Silva, Fábio Silva da; Silva, Sandro Patroca da; Ribeiro Cruz, Ana Cecília; Paiva, Francisco Amilton dos Santos; Casseb, Livia Medeiros Neves; Nascimento, Ana de Nazaré Silva do; Oliveira, Iza Alencar Sampaio de; Branco, Marlon de Araújo Castelo; Oliveira, Rodrigo Adolpho Brasil de; Durans, Darlene de Brito Simith; Paz, Thito Yan Bezerra da; et al. (Frontiers in Veterinary Science, 2023)
The viruses in the Lyssavirus genus are classified into several genotypes (GT1 to GT7), from which, only the GT1 (classic rabies virus -RABV) has a cosmopolitan distribution and circulates in Brazil. The GT1 is subdivided into several antigenic variants (AgV) maintained in independent cycles with a narrow host range and distinct geographic distributions, namely: AgV1 and AgV2 found in dogs, AgV3 vampire bat variant of Desmodus rotundus specie, AgV4 and AgV6 from non-hematophagous bats Tadarida brasiliensis and Lasiurus cinereus species, common variant of marmoset (Callithrix jacchus) and crab-eating fox (Cerdocyon thous). In this study we performed phylogenetic analysis to identify at the antigenic variant level six RABV genomes derived from the Rabies Surveillance from the North and Northeast regions of Brazil. The analysis resulted in the formation of 11 monophyletic clusters, each corresponding to a particular variant, with high bootstrap support values. The samples were positioned within the AgV3, AgV6 and Callithrix sp. variant clades. This the first report of the AgV6 variant found in the northern region of Brazil, which provides valuable information for the rabies surveillance in the country. The possibility of viral spillover has been much debated since it deals with the risk of a transmission shift from a primary host to a secondary one. However, more genomic surveillance studies must be conducted, with larger number and diversity of samples to better understand the transmission dynamics of each variant to detect changes in their geographic distribution and spillover events.